An Evaluation of the Bakhtegan Watershed Sustainability Using the HELP Model - Hamed Kheirandish; Ahmad Sadeghipour; Hananeh Mohammadi Kangarani (پژوهش‌های آبخیزداری, 2021)
Healthily watersheds provide many ecosystem services in various fields, such as social and economic well-being; Therefore, we need to develop methods that can be used to determine the levels of health and sustainability of watersheds. The aim of this research was an evaluation of the sustainability of the Bakhtegan Watershed servicer using the watershed sustainability index (WSI) in a ten year periods of (2006 to 2016). The UNESCO – HELP demonstration has proposed an integrated watershed sustainability index (WSI), based on four criteria of hydrologic (quantity and quality), environmental, life, water policy issues and three parameters of pressure, status and, the response was used in order to achieve low, medium, and high levels of the basin¢s sustainability of services. The results showed that the pressure parameter with a score of 0.75 and the response parameter with the score of 0.45 had the highest and lowest scores for an assessment of the watershed¢s sustainability of services. Furthermore, the results showed that the criterion of quantity hydrological with a score of 0.25 and the environmental quality with a score of 1 offer the most and least priorities for its management. The value obtained for the WSI was 0.61, which represents an intermediate level of basin¢s sustainability of services, thus points to the need for more attention to the region's sustainability level.